Equity Based Crowdfunding: Determinants of Successful Campaign: the Case of Crowdcube Platform in the United Kingdom - Wachira, Virginia Kirigo; Wachira, Esther Wanjiru (Public Finance Quarterly, 2022)
The study is aimed at exploring what influences the amount of money raised which can either lead to the success or failure of equity-based crowdfunding using Crowdcube. The study used Pearson correlations and multiple regression analysis. The regression model was considered a good fit as it was statistically significant. The findings of the paper revealed that the number of investors, target amount, and pre-money valuation strongly and positively influence the success of equity-based crowdfunding campaigns. Additionally, equity, display of share price information, and online social media presence are other factors that influence the success of equity-based crowdfunding campaigns. However, previous crowdfunding history was negatively associated with the success of campaigns. The uniqueness of the study will benefit investors and founders who aim at running or investing in successful equity-based crowdfunding campaigns in the UK and globally. The study recommends further research using other equity-based crowdfunding platforms in different countries and continents.